Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2147/copd.s310319
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Disease Among Exacerbating Patients with COPD Treated with Triple Therapy in Spain

Abstract: Background:The cost of chronic obstructive pulmonary disease (COPD) in Spain has been studied from different perspectives, but parameters such as the patient's phenotype have seldom been considered. Our aim was to describe the disease burden of COPD patients with frequent exacerbator phenotype, treated with triple therapy. Methods: An observational, multicenter study was carried out from December 2017 to November 2018 in pulmonology services among patients ≥40 years with COPD confirmed diagnosis receiving trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This represents approximately 3.0% (n=1287/43,753) of the entire maintenance-treated cohort, which is a slightly higher proportion than the proportion of patients with asthma who have severe, uncontrolled eosinophilic disease despite therapy (<1%), according to a large analysis of patients with asthma who were receiving systemic corticosteroids. 26 Despite the small size of the group, patients with severe, uncontrolled eosinophilic asthma experience a nearly four-fold increase in HCRU events and a four-fold increase in costs (£861.0 vs £222.0 per year) compared with all patients with asthma. 27 This is similar to the findings in our cohort, which revealed that individuals with severe COPD and frequent exacerbations experience a significantly higher number of HCRU events than the general COPD population, even though they are receiving maximal, guideline-directed therapy.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…This represents approximately 3.0% (n=1287/43,753) of the entire maintenance-treated cohort, which is a slightly higher proportion than the proportion of patients with asthma who have severe, uncontrolled eosinophilic disease despite therapy (<1%), according to a large analysis of patients with asthma who were receiving systemic corticosteroids. 26 Despite the small size of the group, patients with severe, uncontrolled eosinophilic asthma experience a nearly four-fold increase in HCRU events and a four-fold increase in costs (£861.0 vs £222.0 per year) compared with all patients with asthma. 27 This is similar to the findings in our cohort, which revealed that individuals with severe COPD and frequent exacerbations experience a significantly higher number of HCRU events than the general COPD population, even though they are receiving maximal, guideline-directed therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings support those of another observational study that demonstrated substantial HCRU, costs, and exacerbation rates among patients with COPD who were receiving triple therapy but continued to experience exacerbations. 26 Of patients who experienced exacerbations despite receiving triple therapy, nearly one-quarter (n=1287/5669; 22.7%) had BEC ≥250 cells/µL and experienced ≥3 exacerbations in the year prior to the index date. This represents approximately 3.0% (n=1287/43,753) of the entire maintenance-treated cohort, which is a slightly higher proportion than the proportion of patients with asthma who have severe, uncontrolled eosinophilic disease despite therapy (<1%), according to a large analysis of patients with asthma who were receiving systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations